1804 Survey of discharge practice and review of safety-netting instructions for children attending Emergency Departments in the UK & Ireland with acute wheeze or asthma: a PERUKI study. Issue 12 (22nd November 2022) - Hannah, Romanie; Chavasses, Richard; Paton, James; Walton, Emily; Roland, Damian; Foster, Steven; Lyttle, Mark
Abstract : Aims, Objectives and Background: Acute wheeze is one of the commonest reasons for childhood Emergency Department (ED) attendances. Ongoing recovery following discharge should be supported with robust safety-netting advice including advice for ongoing bronchodilator use. Evidence for recovery bronchodilator dosing is lacking, likely leading to variation in advice across the UK and Ireland. This study aimed to describe discharge practices, examining consistency and quality of safety-netting advice (including bronchodilator plans) when discharging children with wheeze or asthma, and identify opportunities for improvements Method and Design: This two-phase study was conducted across PERUKI registered sites between June 2020 – September 2021. Phase 1 consisted of single site survey responses regarding departmental discharge practices for acute wheezy presentations. During phase 2, discharge instructions provided for caregivers underwent formal review. Data abstraction tools were developed based upon existing literature regarding written wheeze safety-netting information, BTS/SIGN 2019 asthma guidelines, NICE safety-netting recommendations and the BTS Asthma Discharge Bundle. Results and Conclusion: This two-phase study was conducted across PERUKI registered sites between June 2020 – September 2021. Phase 1 consisted of single site survey responses regarding departmental discharge practices for acute wheezy presentations. During phase 2, discharge instructions provided for caregivers underwent formal review. Data abstraction tools were developed based upon existing literature regarding written wheeze safety-netting information, BTS/SIGN 2019 asthma guidelines, NICE safety-netting recommendations and the BTS Asthma Discharge Bundle. National comparison of discharge practices and written safety-netting information for wheezy children attending EDs showed wide variation. This highlights the need for evidence-based guidance to improve and standardise care, providing consistent discharge and safety-netting advice for carers.